2006
DOI: 10.1897/04-657r.1
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation kinetics and mobility of chlortetracycline, tylosin, and monensin in an agricultural soil in Northumberland County, Ontario, Canada

Abstract: A robust high-throughput method was refined to extract three growth-promoting antibiotics, tylosin (TYL), chlortetracycline (CTC), and monensin (MON), from soil. Analysis was performed by electrospray liquid chromatography tandem mass spectrometry. Soil dissipation rate studies were performed in a farm field soil for antibiotics applied with and without manure. Tylosin, CTC, and MON followed first-order dissipation kinetics with half-lives of 4.5, 24, and 3.3 d, respectively, with the addition of manure and 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
86
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 46 publications
13
86
1
2
Order By: Relevance
“…with previous studies, but could reflect differences in redox conditions or pH between the studies. Most previous studies that have reported chlortetracycline half-lives have investigated dissipation after spiking the compound into soil or manure (Li et al, 2010;Carlson and Mabury, 2006), in contrast to the present study where manure was collected from animals administered chlortetracycline. In contrast, the tylosin half-life reported in this study is consistent with previous studies that measured tylosin half-lives on the order of 4.4 days (Carlson and Mabury, 2006).…”
Section: Fate Of Antimicrobials During Swine Manure Storagementioning
confidence: 85%
See 2 more Smart Citations
“…with previous studies, but could reflect differences in redox conditions or pH between the studies. Most previous studies that have reported chlortetracycline half-lives have investigated dissipation after spiking the compound into soil or manure (Li et al, 2010;Carlson and Mabury, 2006), in contrast to the present study where manure was collected from animals administered chlortetracycline. In contrast, the tylosin half-life reported in this study is consistent with previous studies that measured tylosin half-lives on the order of 4.4 days (Carlson and Mabury, 2006).…”
Section: Fate Of Antimicrobials During Swine Manure Storagementioning
confidence: 85%
“…Most previous studies that have reported chlortetracycline half-lives have investigated dissipation after spiking the compound into soil or manure (Li et al, 2010;Carlson and Mabury, 2006), in contrast to the present study where manure was collected from animals administered chlortetracycline. In contrast, the tylosin half-life reported in this study is consistent with previous studies that measured tylosin half-lives on the order of 4.4 days (Carlson and Mabury, 2006). Kolz et al (2005) measured tylosin degradation in manure slurry under anaerobic conditions, and based on reported decay rates, tylosin half-lives in anaerobic manure ranged from approximately 0.5 to 2 h, shorter than the half-lives measured in the current study.…”
Section: Fate Of Antimicrobials During Swine Manure Storagementioning
confidence: 85%
See 1 more Smart Citation
“…The persistence and movement of antibiotics in the ecosystem have been determined as: sulfonamides and fl uoroquinolones are the most persistent, followed by macrolides; tetracyclines can persist for comparatively extensive ages in the absence of sunlight [27]. Tetracyclines and fl uoroquinolones are easily adsorbed by soils, sediments, and/or manure slurry [2,31]. Estimation in liquid samples is mostly connected to persistence and transport in the marine environment [30,[32][33][34].…”
Section: Fate and Occurrence Of Antibiotics In The Environmentmentioning
confidence: 99%
“…Previous investigation documented a 25-58 days half-life for CTC and 49-76 days for TYL in soil (Halling-Sorensen et al, 2005), a much longer half-life than that observed in the present study. Another investigation comparing the half-life of CTC, TYL, and MNS reported a much shorter half-life in manure-amended and manure-free soil (Carlson and Mabury, 2006); in that study, the calculated half-life in manure-amended soil was 24, 4.5, and 3.3 days for CTC, TYL, and MNS, respectively, and 21, 6.1, and 3.8 days in manure-free soil. The persistence order, CTC > TYL > MNS, in the latter study also differed from that observed in the present study, MNS > CTC > TYL.…”
Section: Resultsmentioning
confidence: 81%